Heterotopic Pregnancy: A Clinical Case Report (Bangladesh Medical Journal, 2012)
Heterotopic pregnancy is coexistence of intrauterine and extrauterine pregnancies that is ectopic pregnancies. It is said to be rare. Here we report a case of 27 years old woman with heterotopic pregnancy. Patient had a typical presentation of severe lower abdominal pain following amenorrhoea for 2½ months. On clinical examination, there was suspicion of ectopic pregnancy but ultrasonography revealed early intrauterine pregnancy along with right tubal pregnancy with huge collection in abdomen . Immediate laparotomy was done and diagnosis was confirmed as a case of heterotopic pregnancy.DOI: http://dx.doi.org/10.3329/bmj.v39i3.9950 BMJ 2010; 39(3)